Evaluating Adherence to National Guidelines and Clinical Outcomes in Staphylococcus aureus Bacteremia. (4th October 2017) - Wooten, Darcy; Seymann, Gregory; Schneider, Beacher; McCauley, Melanie; Taplitz, Randy; Ritter, Michele; Aslam, Saima
Abstract: Background: Variations in adherence to national guidelines for management of Staphylococcus aureus bacteremia (SAB) exist. We evaluated adherence to such guidelines for SAB in an academic hospital and its effect on clinical outcomes. Methods: We conducted a retrospective review of inpatients with SAB between January 2016 and January 2017. We defined 100% adherence to guidelines as completing serial blood cultures, echocardiography, removal of central venous catheters, source control, use of a β-lactam antibiotic for methicillin-sensitive SAB (MSSA), and appropriate duration of antibiotics (2 weeks for uncomplicated SAB and >4 weeks for complicated SAB). The primary outcome was 30-day mortality. Secondary outcomes included 90-day mortality, persistent SAB, relapsed SAB, length of hospital stay, and 30-day readmission. Results: National guidelines were followed in entirety in 71/150 cases (47%, Table 1). Adherence to individual guideline components was variable: serial blood cultures 144/150 (96%), echocardiography 134/150 (89%), removal of central venous catheters 26/34 (75%), source control 57/80 (71%), β-lactam use for MSSA 77/86 (89%), and appropriate antibiotic duration 102/150 (68%). In our multivariate model, adherence to guidelines was not an independent predictor of 30-day mortality or of secondary outcomes with the exception of longer hospital length of stay (LOS). Kaplan-Meier survival curves did not differ based on guideline adherence (Figure 1). Conclusion: Adherence to national guidelines for SAB management was seen in 47% of cases and was not associated with improved clinical outcomes in our retrospective study. This needs to be reassessed in a prospective study to determine relevance in the current era of increasing healthcare costs and requirements to meet specific performance measures. Disclosures: All authors: No reported disclosures.